Enhancement of surfactant performance via titanium dioxide nanoparticles: implication for oil recovery in sandstone - Miftah Hidayat; Miftah Hidayat; Miftah Hidayat; Rima Megayanti; Ndaru Cahyaningtyas; Mahruri Sanmurjana; Zeta Nur Muhammad Yahya; Adityawarman; Adityawarman; Utjok W. R. Siagian; Utjok W. R. Siagian; Taufan Marhaendrajana; et al. (Frontiers in Chemistry)
The application of titanium dioxide nanoparticles in the petroleum research area has received ample attention in recent years owing to its impact on wettability-altering agents. Further, employing a surfactant injection to improve oil production in sandstone formations on an industrial scale has become an alternative solution, particularly for mature fields. However, the existing literature on the combination of alkyl ethoxy carboxylate (AEC) surfactant with titanium dioxide nanoparticles on the application of enhanced oil recovery in sandstone formations remains underreported. This study explores the impact of combining AEC surfactant with titanium dioxide nanoparticles on recovering trapped oil in sandstone by examining the interfacial tension, contact angle, zeta potential, and core flooding with various concentrations of added titanium dioxide nanoparticles (0, 0.01, 0.025, and 0.05 wt%) on AEC surfactant. Although the addition of 0.05 wt% TiO2 to AEC surfactant can significantly reduce the interfacial tension to the lowest value of 5.85 × 10−5 mN/m, our results show that the highest oil recovery in Berea sandstone (59.52% recovery factor) is achieved at the concentration of 0.025 wt% added TiO2 to AEC surfactant. We find that the stability of TiO2 nanoparticles on AEC surfactant plays a significant role in getting maximum oil recovery. These important findings from this study contribute to improving our understanding on the application of TiO2 combined with AEC surfactant to achieve more efficient and sustainable enhanced oil recovery in sandstone.